AN INTEGRATED FRAMEWORK- FOR DESIGNING A STRATEGIC GREEN SUPPLY CHAIN WITH AN APPLICATION TO THE AUTOMOTIVE INDUSTRY - Masoumik, S. Maryam; Abdul-Rashid, Salwa Hanim; Olugu, Ezutah Udoncy; Raja Ghazilla, Raja Ariffin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
In today’s world of global business, several organizations have realized that green supply chain practices provide them with competitive benefits. In this respect, a strategically oriented view of environmental management is critical to supply chain managers. Regarding the importance of this issue, an attempt has been made to develop an integrated framework for designing a strategic green supply chain (SGSC). Firstly, by reviewing the literature, a causal relationship model is developed. This model presents the main factors affecting the decisions for prioritizing green strategies and initiatives. Secondly, based on this model, a decision-making tool using the analytic network process (ANP) is provided. This tool assists companies to prioritize the environmental strategies and related initiatives in different operational areas of their supply chain. Finally, in order to provide part of the data required in this tool, a performance measurement system is developed to evaluate the strategic environmental performance of the supply chain.